Experimental investigations of number of blades effect on archimedes spiral wind turbine performance: Referred to by: https://doi.org/10.31603/mesi.13996 - Agus Dwi Korawan; Rosadila Febritasari (Mechanical Engineering for Society and Industry, 2024)
This study investigates the effect of blade numbers on the performance of Archimedes Spiral Wind Turbines (ASWT), a low-speed axial flow turbine with an Archimedean spiral blade design. Experimental tests and numerical simulations were conducted to evaluate power generation and fluid flow behavior. Results revealed that a three-blade ASWT achieved optimal performance, producing 158.5% more power than the four-blade configuration. The findings highlight the significant influence of blade numbers on ASWT efficiency, offering insights for improving wind turbine design in urban renewable energy applications.